ELMOD documentation: Modeling of flow-based market coupling and congestion management - David Schönheit; Dirk Hladik; Hannes Hobbie; Dominik Möst (ZBW – Leibniz Information Centre for Economics, 2020)
This paper documents ELMOD, a linear optimization model with a nodal pricing approach, covering the energy market and electricity grid of Europe. In the presented formulation, ELMOD is used for the computation of market coupling results without grid constraints and subsequent computation of congestion management, i.e. redispatch and curtailment. Furthermore, flow-based market coupling is implemented, as the EU-stipulated calculation method for cross-border trading capacities. A short case study presents exemplary results for market outcomes based on flow-based market coupling, i.e. n-1 secure trading domains, import-export balances, and zonal prices, as well as necessary congestion management measures.
Keywords: 330; energy system modeling; electricity grid models; linear optimization; congestion management; flow-based market coupling; n-1 security criterion